Enhanced On‐Site Hydrogen Peroxide Electrosynthesis by a Selectively Carboxylated N‐Doped Graphene Catalyst. Issue 20 (2nd September 2021) - Zhang, Yu; Melchionna, Michele; Medved, Miroslav; Błoński, Piotr; Steklý, Tomáš; Bakandritsos, Aristides; Kment, Štěpán; Zbořil, Radek; Otyepka, Michal; Fornaserio, Paolo; Naldoni, Alberto
Abstract: Practical‐scale on‐site production of hydrogen peroxide (H2 O2 ) via two‐electron (2e − ) oxygen reduction reaction (ORR) relies on efficient, robust, and selective electrocatalysts. Among them, carbon‐based materials are cheap, abundant, durable, and their surface properties can be tuned to favor the 2e − ORR pathways, resulting in higher efficiency and facilitating possible scale‐up towards commercially appealing levels. Here, we demonstrate that the selective installment of carboxyl groups on the surface of N‐doped graphene yielding a material named graphene acid (N‐GA) promotes the catalytic 2e − ORR, achieving a H2 O2 faradaic efficiency (FE) as high as 70 % in acidic media (pH=0.96) and a H2 O2 productivity in long term bulk electrolysis that could reach 107.8 mmol gcatalyst −1 h −1 under optimized conditions. Extended XPS analysis and density functional theory (DFT) calculations revealed that surface carboxylic acid functional groups play a significant role in achieving the high activity of N‐GA for 2e − ORR. Abstract : Graphene catalysis : A novel N‐doped graphene derivative with controllable surface carboxylic functionality demonstrates the excellent catalytic activity of oxygen reduction towards H2 O2 generation. The enhancement of performance is due to the terminal −COOH groups.